O processo de elaboração de saberes por professores-pesquisadores de educação física em uma comunidade colaborativa - Sanches Neto, Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the educational theories and public policies oriented towards professionalization of teaching, traversing the notion of teaching professionalism, it is expected that teachers who work in basic education develop their own knowledge in a process of ongoing formation. However, there seems to be some notion of dependency of such teachers to specialists as the theoretical and methodological contributions indicate that mediation between school and university should fit the academic researcher. However, the concept of teacher-researcher could indicate progress in the dimension of thinking beyond the division between school teachers' research and academic researchers. There is the assumption that the practice engenders an epistemology, leaving us - teachers, professors and researchers - to unveil it. Therefore, the general objective is to understand the process of knowledge elaboration by teachers while researching their own teaching practice. It aims to investigate how teachers do organize the teaching and research in relation to school physical education. Thus, the specific objective refer to: identify how teachers organize the teaching and research based on shared knowledge within a permanent and collective process of professional education and development. The qualitative methodological procedures involved collaboration with a group of physical education teachers who reflect collectively on their teaching practices in a kind of autonomous community of teachers. We invited twelve teachers from such community to participate in our research. We have proposed the following techniques to generate and analyze data: documentary source, semi-structured interviews, focus groups, and content analysis. Results indicated that the participants emphasized influence from academic and family relationships in their personal elaboration of knowledge. Towards the research mode, the participants shared predominantly notions on action-research, and...

Résumé: Dans les théories de l'éducation et des politiques publiques orientées vers la professionnalisation de l'enseignement, traversant la notion de professionnalisme, il est prévu que les enseignants à développer leurs savoirs dans un processus de formation continuée. Il semble y avoir une certaine notion de dépendance de ces enseignants à des spécialistes comme les contributions théoriques et méthodologiques indiquent que la médiation entre l'école et l'université doit adapter le chercheur « académique ». Cependant, le concept d'enseignant-chercheur peut indiquer les progrès accomplis dans la dimension de la pensée au-delà de la division entre la recherche des enseignants et des chercheurs universitaires. La pratique engendre une épistémologie, qui nous laissant - enseignants et chercheurs - à dévoiler. Par conséquent, l'objectif général est de comprendre le processus d'élaboration des savoirs par les enseignants en recherchant leur propre pratique. Il vise à étudier la façon dont les enseignants organisent l'enseignement et la recherche à l'école. Ainsi, l'objectif spécifique se rapporte à: identifier comment les enseignants organisent l'enseignement et la recherche fondée sur leurs savoirs partagés au sein d'un processus permanent et collectif d'éducation et développement professionnel. Les procédures méthodologiques qualitatives impliqués collaboration avec un groupe d'enseignants d'éducation physique qui reflètent collectivement sur leurs pratiques dans une communauté autonome. Nous avons invité douze enseignants à participer avec les techniques suivantes pour générer et analyser des données: source documentaire, entretiens semi-structurés, groupes focalisés et analyse de contenu. Les résultats indiquent que les participants ont souligné l'influence des relations académiques et de la famille dans l'élaboration personnelle de savoirs. Vers le mode de recherche, les participants...

Nas teorias educacionais e nas políticas públicas orientadas à profissionalização do magistério, perpassando a noção de profissionalidade docente, espera-se que os professores que trabalham na Educação Básica elaborem seus próprios saberes em um processo de formação permanente. Contudo, parece haver certa noção de dependência desses professores aos especialistas da área à medida que os aportes teoricometodológicos apontam que a mediação entre escola e universidade caberia ao pesquisador acadêmico. No entanto, a concepção de professor-pesquisador poderia indicar avanços na dimensão de se pensar para além da divisão entre pesquisa escolar e acadêmica, ou entre professores-pesquisadores e pesquisadores acadêmicos. Partimos do pressuposto de que a prática profissional engendra uma epistemologia, cabendo a nós - professores e pesquisadores - desvelá-la. Portanto, apontamos como objetivo geral compreender o processo de elaboração de saberes por professores de que pesquisam sua própria prática pedagógica. Tratamos especificamente de investigar o modo como os professores organizam o ensino e a pesquisa em relação à Educação Física na escola. O objetivo específico da nossa investigação remete, assim, a: identificar como os professores organizam o ensino e a pesquisa com base no compartilhamento de saberes em um processo permanente e coletivo de formação profissional. Optamos pela pesquisa qualitativa, envolvendo procedimentos metodológicos colaborativos com um grupo de professores de Educação Física da Educação Básica que buscam refletir coletivamente sobre as suas práticas em um tipo de comunidade autônoma de professores. Convidamos doze participantes dessa comunidade para nossa pesquisa. Para a geração e a análise dos dados junto aos participantes propusemos como técnicas: fonte documental, entrevista semiestruturada, grupo focal e análise de conteúdo. Os resultados indicaram que...
Keywords: Teachers, Training of; Professores - Formação; Pratica de ensino; Documentação; Ensino - Organização; Pesquisa - Organização; Educação física - Estudo e ensino; Pesquisadores